Environmental constraints on the lipid composition and metabolism of euphausiids:the case of Euphausia superba and Meganyctiphanes norvegica - Mayzaud, P; Albessard, E; Patti Virtue; Boutoute, M (2000)
Antarctic (Euphausia superba) and northern krill (Meganyctiphanes norvegica) are characterised by largescale spatial distributions. Euphausia superba is limited to the Southern Ocean, while M. norvegica is present from the Arctic Ocean to the Mediterranean Sea. Euphausia superba structural lipids showed little mesoscale variability. Specific differences between phosphatidylcholine and phosphatidylethanolamine fatty acid composition exceeded variability related to sampling stations. On a larger scale (Southern Ocean), fatty acid composition of both total polar lipids and phosphatidylcholine confirmed the reduced level of regional variability. Similar comparisons between female M. norvegica collected at two extreme sites in terms of temperature regime (Kattegat and Ligurian Sea) during two seasons (spring–summer and fall–winter) suggested a more complex picture. Levels of phosphatidylethanolamine, lysophosphatidylcholine, and diphosphatidylglycerol showed significant differences between sites. During spring– summer, a lower content of phosphatidylethanolamine and lysophosphatidylcholine was observed for the Ligurian Sea population. Fatty acid composition of total polar lipids was significantly different at both sites. Comparisons between spring–summer populations at both sites showed higher percentages of 22:6n–3 and a lower content in saturated and monoenoic acids for the Ligurian Sea, suggesting some degree of adaptation to temperature regime. 103